Decision Making Method Based on Paraconsistent Annotated Logic and Statistical Method: a Comparison - Carvalho, Fabio Romeu de [UNESP]; Brunstein, Israel [UNESP]; Abe, Jair Minoro [UNESP]; Dubois, D. M. (Amer Inst Physics, 2008)
Presently, there are new kinds of logic capable of handling uncertain and contradictory data without becoming trivial. Decision making theories based on these logics have shown to be powerful in many aspects regarding more traditional methods based on Statistics. In this paper we intend to outline a first study for a decision making, theory based on Paraconsistent Annotated Evidential Logic ET (Paraconsistent Decision Method (PDM)) and classical Statistical Decision Method (SDM). Some discussion is presented below.
Keywords: Decision making; paraconsistent annotated logic; para-analyzer algorithm; level of requirement; non-classical logics